The anglophone problem in Francis Nyamnjoh's ethnographic fiction: negotiating nationalism, belonging and flexible Cameroonian citizenship - Loombe, Leon Bomela (Department of English Language and Literature, 2025)
The Anglophone Problem in Cameroon encapsulates deeply entrenched linguistic, cultural, and political tensions stemming from the historical marginalisation of Anglophones by the Francophone-dominated government. Despite official denials, Anglophone grievances are rooted in the government's failure to honour the 1961 Constitution, which established a federal structure recognising the equal status of Anglophone and Francophone regions (Konings & Nyamnjoh, 2003). The enforced unification of political parties into a single entity in 1966 (Ambanasom, 2013) and the abolition of federalism in 1972 contravened these constitutional principles, entrenching Francophone dominance. This marginalisation was further intensified in 1984 when a referendum rebranded the nation as “La République du Cameroun,” effectively erasing Anglophone identity as an equal partner in the union (Manjoh, 2028). Francis Beng Nyamnjoh is as an Anglophone Cameroonian writer and ethnographer. His ethnographic fiction portrays the shared struggles of individuals within a fragmented society, emphasising the dynamic and dialectical nature of their relationships. This study examines how Nyamnjoh addresses the complexities of belonging in this context, focusing on his eight novels: Mind Searching (1991), The Disillusioned African (1995), A Nose for Money (2006), Souls Forgotten (2008), The Travail of Dieudonné (2008), Married but Available (2009), Intimate Strangers (2010), and Homeless Waters (2011) through the lens of ethnographic fiction. It explores his depiction of the Anglophone issue, investigating themes of nationalism, belonging, and citizenship in Cameroon. By critically analysing the imaginary Mimboland setting of these novels as an allegory of Cameroon, and the allegorical citizenship of Mimbolanders, the study delves into the intricate process of identity formation and the socio-political challenges arising from Cameroon's postcolonial history, where Anglophone Cameroonians endeavour to secure their place within the broader national framework. Through this literary analysis, I argue that Anglophones must navigate a delicate balance of cultural loyalty, political alignment, and the pursuit of a more inclusive national citizenship. Nyamnjoh's fiction, in this context, reflects on contested concepts of belonging, national identity, and the fluid nature of citizenship within Cameroon's divided linguistic landscape. Ultimately, this dissertation sheds light on the ongoing quest for recognition and self-determination amidst the complex and evolving socio-political realities of Cameroon.